Studying the relationship between students' self-efficacy and social adaptation - Namier Ulziibayar (Lavai)
This study examined the relationship between student self-efficacy and social adaptability. Our research is innovative in that it examines the relationship between social adaptability and self-efficacy, which is one of the soft skills considered to be important skills of the 21st century. 2,713 students from five universities of Inner Mongolians participated in the study. According to the results of the research, the student's social adaptation in 7 parameters (learning, "I" with people, professional choice, self-reliance in life, environment, somatic mental characteristics) is above average or good (M=3.68), self-efficacy is above average for all students (M=2.58). Also, according to the results of the T-test analysis of self-efficacy, there is a difference between genders (p = 0.001), i.e. male students have higher self-efficacy and social adaptation. The total score of social adaptation of male and female students (p = 0.049) and their environment overall acceptance (p=.001) is different depending on gender, the total score of social adaptation (p=.008) and learning adaptability (p=.000), adaptability with people (p= .010), adaptability of "I" (p=.000), adaptability to career choice (p=.009) are different to a certain extent. Also, social adaptation and self-efficacy have a moderately positive correlation (r=.329), and self-efficacy affects social adaptation by 10.8% (ΔR² = 0.108).